Nationwide epidemiological study of subarachnoid hemorrhage: trends in admissions, mortality, seasonality, costs, clipping, embolization, and the impact of COVID-19 - Goulart, Thiago Oscar; Marazzi, Thire Baggio Machado; Monteiro, Rosane Aparecida; Perdoná, Gleici da Silva Castro; Camilo, Millene Rodrigues; Pontes-Neto, Octávio Marques (Frontiers in Neurology, 2025)
IntroductionAneurysmal Subarachnoid Hemorrhage (aSAH) represents a severe neurological emergency with high morbidity and mortality. Despite advances in neurocritical care and endovascular techniques, aSAH remains a significant burden, especially in resource-limited settings like Brazil, where studies of this condition are scarce until now. This study evaluates the epidemiology, costs, and procedural trends of aSAH in Brazil from 2017 to 2022, highlighting the impacts of the COVID-19 pandemic.MethodsThis retrospective study analyzed secondary data from the Brazilian public health system (DataSUS) using ICD-10 code I60 for aSAH. Key metrics included the evaluation of admissions with time-series in Python, and mortality rates, procedures, and costs.ResultsBetween 2017 and 2022, 61,134 aSAH admissions were recorded, averaging 10,189 annually. The in-hospital mortality rate remained consistently high at 20.3% (range: 19.2–20.5%), with 12,192 total deaths. Admissions declined temporarily during the initial of Pandemic (April–June 2020) but later recovered. Seasonal admission peaks were observed in mid-year months (June–August), while December–February consistently showed lower rates. The average length of hospital stay was 10.0 days, with a decline during the pandemic (9.6 days in 2020) before stabilizing post-pandemic. This pattern likely reflects pandemic-related disruptions and early discharges to manage hospital bed shortages. Procedures for ruptured aneurysms included 8,290 embolizations (13.8%) and 3,043 neurosurgical clippings (5.0%), treating 18.8% of admissions. During the pandemic, procedural volumes declined, with faster recovery in embolizations compared to clippings. Total hospitalization costs were BRL 397,665,436.57 (US108 million), with an annual increase from BRL 62 million in 2017 to BRL 71 million in 2022. Costs per patient were significantly higher for aSAH compared to other cerebrovascular conditions, reflecting the complexity of care.ConclusionThis comprehensive analysis highlights the clinical and economic challenges of managing aSAH in Brazil. While admissions and mortality rates remained stable, the pandemic disrupted care delivery and procedural volumes. Low rates of aneurysms secured underscore disparities in access across Brazil. Rising costs emphasize the need for investments in preventive measures, equitable treatment access, and healthcare system resilience. Future strategies should focus on expanding stroke unit coverage and addressing modifiable risk factors to reduce the burden of aSAH.